Intrathyroidal branchial cleft cyst: a case report - Vaidhyswaran, Roopak; Jothivel, Jayavarshini; Natarajan, Kiran; S., Raghu Nandhan; Kameswaran, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Intrathyroidal branchial cleft cyst is a rare entity in otolaryngology practice with few cases reported in the literature. Clinically, it mimics a thyroid swelling and the diagnosis is confirmed only by histopathology. The cyst walls are lined by predominantly non-keratinizing stratified squamous epithelium with characteristic subepithelial lymphoid tissue. This is a case report of right intrathyroidal branchial cleft cyst in a 50-year-old and a left intrathyroidal branchial cleft cyst in a twelve- year-old boy. Both patients underwent imaging followed by surgical management. A fourth branchial cleft cyst is very rare and may have varied presentation. Both patients with intrathyroidal branchial cleft cysts had complete surgical excision and are normal during regular follow ups. The presentation of a fourth branchial cleft cyst may occur as an intrathyroidal swelling. The recommended treatment of an intrathyroidal branchial cleft cyst is complete surgical excision of the branchial cyst with thyroidectomy. Misdiagnosis of a fourth branchial cyst can result in incomplete removal leading to recurrence. Awareness about the clinical manifestations of a fourth branchial anomaly is crucial for appropriate management.